Sustainable packaging transitions in cement production: Exploring circular economy pathways and intergenerational justice in emerging economies - Shanta, Mehedi Hasan; Tanha, Tasfia; Roshid, Md.Mustaqim; Meinhold, Roman; Marcão, Ricardo; Santos, Vasco; Martinho, Filipa; Waaje, Abdul (Discover Sustainability, 2026)
Achieving sustainability in resource-intensive industries such as cement production requires a transition away from synthetic plastic packaging toward biodegradable alternatives that reduce long-term environmental harm. This study evaluates and ranks feasible biodegradable packaging options for cement manufacturers using an integrated multi-criteria decision-making (MCDM) framework. Entropy and Criteria Importance Through Intercriteria Correlation (CRITIC) weighting techniques are combined with the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR), and the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE II) to assess materials across biodegradability, recyclability, lifecycle impacts, and cost performance. Across all methods, cornstarch-based packaging consistently ranked highest, scoring roughly 25–30% better than alternative materials on biodegradability and lifecycle indicators. Despite its strong environmental profile, higher production costs and weak regulatory support remain significant obstacles to adoption, especially in emerging economies. These findings point to the need for targeted incentives, such as subsidies, tax benefits, and clearer standards, to make biodegradable packaging financially viable at scale. The study offers a practical decision framework for industry and policymakers while emphasizing the ethical importance of ensuring that packaging innovations contribute to intergenerational justice and long-term sustainability.